Kajian Investigasi Penerapan Building Information Modelling (BIM) pada Sektor Konstruksi di Kota Palangka Raya - Uda, Subrata Aditama Kittie Aidon; Uda, Saritha Kittie; Devia, Devia (Politeknik Negeri Lhokseumawe, 2025)
The construction industry is witnessing a rapid and sophisticated advancement in technology and information, which has led to intense competition among construction service providers. One of the technologies that has completely changed the construction sector is Building Information Modelling (BIM). Acquiring proficiency in this approach will boost productivity and enhance time, expense, quality, and environmental friendliness. Nonetheless, there is still a lack of discernible progress in the application of BIM in the construction industry, particularly for contractors and consultants residing outside of Java Island. This research was conducted in the city of Palangka Raya where most of the construction service actors still use conventional methods, this will provide an opportunity to find out the responses and obstacles experienced by local construction service actors regarding the use of BIM in construction work. The results showed that the advantage factor was occupied by the cost and time management sub-factor with a mean value of 4.158 and a standard deviation of 0.449, while the obstacle factor was the BIM support facility with a mean value of 4.422 and a standard deviation of 0.666 as the dominant factor inhibiting the implementation of BIM in construction projects in Palangka Raya City. The government's participation in enhancing contractors' and consultants' capacity to understand BIM through training and competency programs is necessary to foresee this hindrance factor.